(untitled) (Web of Teachers: Inderscience Research, 2024)
The development of new teaching methods in accordance with the new state educational standards should help to obtain fundamental education that contributes to the further development of the individual. It is necessary to give a panorama of the most universal methods, laws and models of modern physics, to demonstrate the specifics of the rational method of cognition of the surrounding world, to focus on the formation of students ’ General physical Outlook and the development of physical thinking.